Detection of Potential Zoonotic Agents Isolated in Italian Shelters and the Assessment of Animal Welfare Correlation with Antimicrobial Resistance in Escherichia coli Strains - Antonio Cocco; Alessandra Alessiani; Romolo Salini; Federica Iapaolo; Daniela Averaimo; Cinzia Pompilii; Giovanni Foschi; Fabio Bellucci; Filomena Iannino; Paolo Dalla Villa; Anna Janowicz; Marco Caporale (MDPI AG, 2023)
Welfare conditions in shelters, where dogs might be housed for a long period of time, may have a possible correlation with the occurrence of bacterial pathogens and their antimicrobial resistance (AMR). In this study, we assessed the occurrence of AMR in 54 strains of Escherichia coli isolated from dogs housed in 15 Italian shelters and we correlated the resistance patterns to animal welfare. We also aimed to evaluate the presence of specific pathogens with zoonotic potential in sheltered dogs. Thus, nasopharyngeal, rectal, and oral swabs were collected from a group of 20 dogs in each shelter and totaled 758 swabs. We identified 9 Staphylococcus pseudointermedius, 1 Pasteurella multocida, 9 Staphylococcus aureus, 12 Campylobacter spp., 54 Escherichia coli, 2 Salmonella enterica, and 246 Capnocytophaga spp. The antimicrobial susceptibility was assessed for the E. coli isolates using a panel of 14 antibiotics. The highest level of relative AMR was recorded for ampicillin and sulfamethoxazole. The association found between AMR and the levels of animal welfare scores in shelters was evident although not statistically significant. These results support the hypothesis that the good management of shelters can increase the level of animal welfare, thus reducing the use of antibiotics and, as a consequence, the AMR occurrence found in dogs that share their domestic environment with humans.